Association between telomere length and complete blood count in US adults - Mazidi, Mohsen; Penson, Peter; Banach, Maciej (Archives of Medical Science, 2017)
Introduction : Telomere length (TL) is related to age-related health outcomes, but little is known about the relationship between TL and complete blood count (CBC) parameters. We aimed to determine the relationship between TL and CBC in a sample of healthy US adults. Material and methods : Participants in the National Health and Nutrition Examination Survey (NHANES) recruited between 1999 and 2002 who had essential data on total CBC and TL were studied. We computed age- and race-adjusted mean values for total CBC using analysis of covariance (ANCOVA). All statistical analyses accounted for the survey design and sample weights by using SPSS Complex Samples v22.0 (IBM Corp, Armonk, NY). Results : Of the 8892 eligible participants, 47.8% (n = 4123) were men. The mean age was 41.8 years overall, 41.0 years in men and 42.6 in women (p = 0.238). The sex-stratified ANCOVA showed no significant difference in the total CBC across TL quartiles (all p > 0.05) in both sexes. In the adjusted model, there was a significant negative relationship with monocyte count ( = –0.051, 95% CI: –0.422; –0.142), mean cell hemoglobin ( = –0.051, 95% CI: –0.038; –0.011) and red cell distribution width ( = –0.031, 95% CI: –0.054; –0.003), while there was a significant positive relationship with basophil ratio ( = 0.046, 95% CI: 0.049–0.171). Conclusions : These results support the possibility that telomere attrition may be a marker for reduced proliferative reserve in hematopoietic progenitor cells.